Targeting the type III secretion system to treat bacterial infections. (February 2014) - Marshall, Natalie C; Finlay, B Brett
<x xml:space="preserve">Abstract</x> Introduction: Causative agents of pneumonia, gastroenteritis, typhoid fever, and plague all utilize a type III secretion system (T3SS) to directly inject proteins into human cells and cause disease. These bacterial pathogens are frequently resistant to antibiotics and novel treatment options are needed. The T3SS is essential for virulence and can be inhibited to prevent disease. Areas covered: T3SS structure and assembly are introduced in this review, highlighting targets for T3SS-specific therapeutics. Promising inhibitors of type III secretion (T3S), their modes of action, and successful techniques for their identification are reviewed. T3S inhibitor research has focused on small molecules identified in high-throughput screens, although recently inhibitors have also been identified or engineered by rational design. Promising compounds have emerged that inhibit T3S and attenuate virulence in several pathogens, including an engineered antibody in clinical trials. T3S inhibitor research may yield effective treatments and prophylactics that are effective against a wide range of human pathogens. Expert opinion: More techniques are needed to identify the mode of action for compounds identified in high-throughput screens, a long-standing challenge. Although only a few groups have attempted rational design of inhibitors, the approach has seen initial success and mechanistic follow-up studies are greatly simplified.